Typology of Religiosity among Youth in Isfahan - Alireza Shojaee Zand; Arash Hasanpour (جامعه شناسی کاربردی, 2014)
Introduction With regard to the significance of religion in Iran, diversity and pluralism which have existed in religiosity as a social- humanistic affair itself, and changes that have taken place in quality of religiosity in recent years, this study tries to provide a typology of religiosity among youth in Isfahan city. Types of religiosity challenges the dual context of either being religious or not being religious in this arena. Indeed, this study, accepting the presupposition that religiosity is a varied, diverse and instable issue, tries to investigate most common types of religiosity and their frequency, regardless of its reasons (emergence of different typology of religiosity). Overall, this study addressed the following questions: What are different types of religiosity among youth in Isfahan? How can be criticized the studies done on typology of religiosity inside the context of Iran? What is a proper logical rationale for typology of religiosity? Note that in this study, religiosity, in general terms, means having religious efforts in a way that attitudes, tendencies, and actions of an individual are influenced. It can also be stated that religiosity is having religious concerns (ShojaeeZand, 1384, p. 4). Materials and Methods The present study made use of deductive and inductive methods for studying typology and quantitative and qualitative methods for investigating typology of religiosity. In other words, this study tried to answer its questions using mixed method research design. To achieve this goal, quantitative and qualitative methods were mixed in a form of one methodology or a multi-phase study. In terms of typology, this study followed two inductions and one deduction. Two inductions used in this study were 1) induction of typologies done in Iran 2) religious induction of actors to identify their religiosity. This study was based on grounded theory in terms of qualitative framework. To collect qualitative data, interview technique was used. Interviews were carried out semi-structurally. In terms of sampling, like other qualitative researches, it was based on purposive sampling technique. To analyze data in the framework of grounded theory, based on Strauss & Corbin (1385), findings were openly coded (deriving basic concepts), then axially coded (deriving major categories) and finally selectively coded (defining core categories- final). At the end, core categories (eight types of religiosity) were identified. After conducting interviews and passing the induction phase of the study, based on analysis of interviews and identification of types of religiosity, we proceeded to a deductive phase, in which it was tried to define and operationalize the identified types obtained through qualitative interviews. So we prepared a measurement scale to investigate the status of obtained types among the given population. To have a sample representative of the population, it was tried to have classified random sampling proportional to population of each of 14 districts of the city. To determine the size of the sample, a pilot test was administered and 321 participants were selected using Cochranâs formula. Discussion of Results & Conclusions A. Qualitative Findings: Following three-phase analysis and codification of qualitative interviews eight types of religiosity were identified. 1. Devotional: the type of religiosity in which individuals make their utmost effort to do Vajib (obligatory) acts like saying prayers and fasting and emphasizing commitment to them. 2. Ritualistic: in this type, religious person tends and makes especial efforts to take part in group acts like saying congregational prayers (Salat-al-Jamaâat) in mosques and other religious places. 3. Feqhi: the type of religiosity in which people have especial commitment to imitate ahkam and ancillaries of the faith from their Marja. 4. Self-referential: the religiosity of those who largely care about individuality and self-recognition. This group interpret religion based on their own interpretation and subsequently accept some instructions, components and ahkam selectively, while rejecting others. 5. Pure heart: This group considers religiosity an inner affair and put emphasis on having pure intention and character. And this satisfies their religiosity. 6. Moralistic: A type of religiosity whose followers lay emphasis on morals, humanity, general conscience among all, wellness and peaceful coexistence. 7. Tavassoli: religiosity of those who consistently resort to Prophets and Imams and ask from them to fulfil their needs and desires 8. Synthetic: a type of religiosity in which individuals are active seekers who curiously search religions, sects and mystical trends and look for something new besides their previous established religion. B. Quantitative Findings: Based on the results, different types of religiosity can be described as follow: 16.7% of participants are ritualistically religious, 15.5%, are Feqhi, 14.8%, are moralistic, 11.7%, are pure heart, 11.4% are Tavassoli, 9.8%, are self-referential, and 5.7% are synthetically religious. Consequently, two clusters of religiosity were identified using cluster analysis. In the first cluster, Total religiosity, 189 (59%) of youth including four types of Devotional, Ritualistic, Feqhi and Tavassoli were placed. In second cluster, namely, self-recognition religiosity which consists of Self-referential, pure heart, moralistic religiosity, 128 (41%) of the participants were grouped. It should be explained that although true religiosity initially specified larger proportion of youth to itself, a slow and rather serious movement of self-recognition followers is prominent and worth investigating. It indicates a change in social and cultural structure of society in general and youth in Isfahan in particular.